Avanafil - a further step to tailoring patient needs and expectations. Issue 9 (1st September 2016) - Boeri, Luca; Capogrosso, Paolo; Ventimiglia, Eugenio; Serino, Alessandro; La Croce, Giovanni; Russo, Andrea; Damiano, Rocco; Montorsi, Francesco; Salonia, Andrea
ABSTRACT: Introduction : Phosphodiesterase type 5 inhibitors (PDE5Is) represent the first-line treatment for erectile dysfunction (ED). Almost one in two patients, however, show some level of treatment dissatisfaction and up to 30% fail to respond to any of the currently available PDE5Is. Recently, the second-generation PDE5I avanafil was launched for the treatment of ED. Areas covered : Pivotal studies of clinical development along with placebo-controlled randomized clinical trials (RCTs) of avanafil in patients with ED were reviewed. Studies concerning the pharmacokinetics and pharmacodynamic of the drug were also analysed. A systematic literature search for English-language studies published up to May 2016 using the Medline database was performed. The search included the terms avanafil and ED. Expert commentary : Avanafil is a potent, highly selective PDE5I whose efficacy is comparable to that of currently available PDE5Is in both naïve and previous PDE5I users. Avanafil is effective within approximately 15 minutes of dosing, thus representing the only PDE5I approved for as-needed use, 15 to 30 minutes before sexual activity. Avanafil has high selectivity for the PDE5 isoenzyme, thus resulting in a lower incidence of drug-related side effects compared to other PDE5Is.